Imaging hematomas in unforeseen sites - unveiling 2 cases of pediatric scurvy - Yew, Ting Ting; Lui, Tjun Hoe; Abdul Qayyum, Abdul Rahman; Lim, Aun Nee; Tan, Sue Lyn (Springer Nature, 2026)
Background Scurvy, a nutritional disorder resulting from chronic deficiency in vitamin C, is now a rare occurrence in contemporary times. Nevertheless, instances can still arise in pediatric patients, typically linked to inadequate nutrition and socioeconomic factors. Diagnosing scurvy proves challenging due to its infrequency and nonspecific symptoms. Clinical and radiographic findings, coupled with low serum vitamin C levels, are crucial for diagnosis. Pediatric scurvy often exhibits prominent musculoskeletal manifestations with varying presentations. Case presentation We present two cases of pediatric scurvy, wherein subperiosteal hematomas were identified on MRI, initially misdiagnosed as infections and abscesses. Both patients responded positively to vitamin C supplementation, and in one case, resolution of the hematoma was observed on MR imaging. Conclusions Musculoskeletal manifestations, particularly subperiosteal hematomas, serve as significant indicators for diagnosing pediatric scurvy. Timely identification is crucial, as proper treatment yields an excellent prognosis.